2021
DOI: 10.1186/s11671-021-03506-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Metal Oxide Electrode for CIGS Solar Cells: The Application of an AgOX Wetting Layer

Abstract: Oxide/metal/oxide (OMO) layer stacks are used to replace transparent conductive oxides as front contact of thin-film solar cells. These multilayer structures not only reduce the overall thickness of the contact, but can be used for colouring of the cells utilizing interference effects. However, sheet resistance and parasitic absorption, both of which depend heavily on the metal layer, should be further reduced to reach higher efficiencies in the solar cells. In this publication, AgOX wetting layers were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…This improvement was possible due to two effects: First, the application of the AgO X wetting layer was successfully integrated in the OMO electrode also on module level, resulting in both lower sheet resistance and higher transmission of the electrode. 11 Second, in contrast to the previously studied cells, the modules presented here were n AZO $ 2.0, n foil $ 1.7, n glass $ 1.6 and n air $ 1.0, the encapsulation reduces the reflection similar to an antireflection layer. 13 Consequently, more light is transmitted into the cell and a higher current is generated.…”
Section: Front Contacts With Integrated Colourmentioning
confidence: 87%
See 3 more Smart Citations
“…This improvement was possible due to two effects: First, the application of the AgO X wetting layer was successfully integrated in the OMO electrode also on module level, resulting in both lower sheet resistance and higher transmission of the electrode. 11 Second, in contrast to the previously studied cells, the modules presented here were n AZO $ 2.0, n foil $ 1.7, n glass $ 1.6 and n air $ 1.0, the encapsulation reduces the reflection similar to an antireflection layer. 13 Consequently, more light is transmitted into the cell and a higher current is generated.…”
Section: Front Contacts With Integrated Colourmentioning
confidence: 87%
“…An AgO X wetting layer was used to increase homogeneity and conductivity of the Ag layer. 11 Prior to deposition of the electrodes, the sputter rates of the AZO deposition processes were determined by thickness measurements single-layer reference samples on glass substrates with a relative error of 2%. To determine the deposition rate of silver, samples with a sandwich of two AZO layers with and without a silver layer inbetween were prepared.…”
Section: Front Contact With Integrated Colourmentioning
confidence: 99%
See 2 more Smart Citations
“…An improved electrode with the implementation of a wetting layer enabled a PCE of about 13%. [339] Stimulated by the pioneering work of Kats, Capasso and co-workers on strong interference effects in highly lossy media, [80,340] many relevant demonstrations of decorative PV based on optical absorbing resonant nanocavity have been realized. Lee et al showed a colored ultrathin PV with subwavelength a-Si absorber below 30 nm embedded between two reflective metal electrodes (Figure 6g).…”
Section: Opaque Colored Solar Cell Technologiesmentioning
confidence: 99%